2011
DOI: 10.1055/s-0039-1698913
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Distribution of Idiopathic Osteosclerosis of the Jaw

Abstract: Objectives:To determine the prevalence of idiopathic osteosclerosis (IO) in the jaw by radiographic evaluation and to investigate the relationship between the findings in relation to age, gender, and localization.Methods:The study included 2,211 panoramic radiographs obtained from the patients (915 men and 1,296 women) whose ages ranged from 10–77 and who visited the Department of Oral Diagnosis and Radiology in the Faculty of Dentistry, Erciyes University between 2008 and 2009.Results:Of 2,211 patients, 135 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 11 publications
6
52
0
16
Order By: Relevance
“…Many studies investigated among various populations by different radiographic equipment reported the distribution of IO between % 1.7 and % 31 mostly without gender discrimination and with mandibular posterior predominance (1)(2)(3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The difference in ethnic groups living different geographic regions; having distinctive genetic variations, habits and addictions was implied for one of the reasons of this distribution discrepancy in addition to unstandardized IO description between investigators and difference in radiographic technique of choice (3,6,15,16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies investigated among various populations by different radiographic equipment reported the distribution of IO between % 1.7 and % 31 mostly without gender discrimination and with mandibular posterior predominance (1)(2)(3)(4)(5)(6)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The difference in ethnic groups living different geographic regions; having distinctive genetic variations, habits and addictions was implied for one of the reasons of this distribution discrepancy in addition to unstandardized IO description between investigators and difference in radiographic technique of choice (3,6,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkish population; IO distribution was reported between 2.4% and 6.1% on the studies performed with panoramic radiography [18][19][20][21] and 4% of 500 patients on a study performed with CBCT (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mandibular region, it frequently occurs in posterior region when compared to anterior region 5 . It is observed incidentally in radiographs as a well defined radiopacity ranging in size from 2mm to more than 2 cm, and is elliptical, round or irregular in shape 6 . They can be observed at apex of tooth roots or between the teeth roots.…”
Section: Discussionmentioning
confidence: 99%